Pengembangan Bahan Ajar Cetak Berorientasi Kearifan Lokal dalam Materi “Negaraku Indonesia” pada Siswa Kelas IV SDN 14 Pontianak Selatan - Vivi Niyarti; Asmayani Salimi; Dyoty Auliya Vilda Ghasya (Journal on Education, 2024)
This research and development aims to produce local wisdom-oriented printed teaching material products in the material "My Country Indonesia" for grade IV elementary school students that are valid and feasible to use to assist the learning process in the independent curriculum. The method used is the Research and Development (R&D) method by adapting the 4-D model. The sample of this study was 3 validators on the material aspect obtained an average of 3.80 with the criteria "Very Feasible", the language aspect obtained an average of 3.53 with the criteria "Very Feasible", and the design aspect obtained an average of 3.20 with the criteria "Feasible" for the local wisdom-oriented printed teaching materials developed. These results are supported by the results of development trial activities based on teacher responses which obtained a percentage value of 100% with the criteria "Very Good" and student responses of 87.12% with the criteria "Very Good". The results showed that grade IV students were interested and understood the local wisdom-oriented printed teaching materials because the teaching materials developed adjusted the local culture of West Kalimantan. So it can be concluded that local wisdom-oriented printed teaching materials are suitable for use in the learning process.